x²- 3x^2- 9x - 5 factorize
Answers
Answered by
0
Answer:
x³ - 3x² - 9x - 5
= x³ + x² - 4x² - 4x - 5x - 5
= x²( x + 1) - 4x ( x + 1) - 5(x + 1)
= (x + 1)(x² - 4x - 5)
= (x + 1)(x² -5x + x - 5)
= (x + 1)(x - 5) (x + 1)
hence, (x +1), (x -5) and (x +1) are the factors of given polynomial .
Answered by
1
Answer:
x^2-3x^2-9x-5
-2x^2-9x-5
-2x^2-10x+x-5
-2x(x-5)+1(x-5)
(-2x+1)(x-5)
Step-by-step explanation: By middle term splitting
Similar questions
Math,
6 months ago
Math,
6 months ago
English,
1 year ago
Political Science,
1 year ago
Science,
1 year ago